Translation and cross-cultural adaptation of the Air Medical Prehospital Triage (AMPT) Score for Helicopter Transport of Trauma Patients to Brazilian Portuguese - Alvim-Oliveira, Roges; Bernardes-Oliveira, Camila L.; Reis, Aline S.; Brown, Joshua B.; Sá-Caputo, Danúbia C.; Bernardo-Filho, Mario (Brazilian Journal of Health and Biomedical Sciences, 2022)
Introduction: The transport of patients by airplanes or helicopters reduces treatment time, while improving the chances of survival and the quality of life. Due to its costly maintenance and operation service, the air transport of victims depends on appropriate triage criteria for patients eligible for this type of transport. The Air Medical Prehospital Triage (AMPT) Score for Helicopter Transport of Trauma Patients quickly classifies the likelihood of trauma victims benefiting or not from helicopter transport. Objectives: The aim of this study was to translate the AMPT Score and cross-culturally adapt it to Brazilian Portuguese. Methods: This study followed international guidelines for standardized translation processes and was developed from: translation, synthesis, back translation, assessment of equivalences by the expert committee, proposal of the previous version of AMPT Score, application of pre-test/post-test and proposition of the final version of the translated scale. Results: The Wilcoxon Test comparing the experts’ assessment with the positive expected resulted in a p-value = 0.0625 (General) CI 95%. The Content Validity Index (CVI) of the experts committee was calculated as 0.9479. The pre-test data resulted in a Cronbach’s Alpha of 0.920 ± 7.26. The free-marginal Kappa coefficient of pre-test data was 0.89 (95% CI for 0.86, 0.93). The post-test data resulted in a Cronbach’s Alpha of 0.925 ± 5.36. The Wilcoxon Test comparing pre-test with post-test resulted in a p-value of 0.0942. Conclusions: The process resulted in a translation of the AMPT Score with the appropriate equivalences proposed by the literature that is statistically reliable and will be of great value to professionals who work with transporting trauma victims in helicopters. Keywords: Prehospital care; Air ambulances; Helicopter; Triage; Translation.